Exponential signaling gain at the receptor level enhances signal-to-noise ratio in bacterial chemotaxis - Neumann-Pfeifer, Silke; Løvdok, Linda; Bentele, Kajetan; Meisig, Johannes; Ullner, Ekkehard; Paldy, Ferencz S.; Sourjik, Victor; Kollmann, Markus (PLOS ONE, 2014)
Cellular signaling systems show astonishing precision in their response to external stimuli despite strong fluctuations in the molecular components that determine pathway activity. To control the effects of noise on signaling most efficiently, living cells employ compensatory mechanisms that reach from simple negative feedback loops to robustly designed signaling architectures. Here, we report on a novel control mechanism that allows living cells to keep precision in their signaling characteristics - stationary pathway output, response amplitude, and relaxation time - in the presence of strong intracellular perturbations.